The Role of the Constitutional Court As A Guardian of the Balance of Power Between State Institutions - Siti Fatia Nazela (Dinasti Research, 2026)
Indonesia is a constitutional democracy with a system of government strictly regulated by the 1945 Constitution. In the Indonesian government's structure, the Constitutional Court plays a key role in maintaining the balance of power. The Constitutional Court is tasked with ensuring that the powers granted to state institutions, including the Executive, Legislative, and Judiciary, are not overlapped or abused and ensuring that all policies and actions are in line with the constitution. The 1945 Constitution mandates that the Constitutional Court carry out its main task: to test the Law against the 1945 Constitution, within the system of checks and balances, so that the Constitutional Court becomes a vital organ in maintaining legal stability and the balance of power between state institutions. In practice, the Constitutional Court faces many challenges from political or external interests that affect its policies and decisions. This research aims to discuss the Constitutional Court's role in supervising the power of state institutions to prevent abuse of authority that could harm the community and damage the Indonesian legal system. This research uses a normative juridical approach with descriptive analysis, based on laws and regulations, Constitutional Court decisions, and other related literature. The results of this research conclude that the Constitutional Court not only functions to maintain the supremacy of the constitution, but also serves as a bridge to balance power among state institutions with their own authority.